Review of the Implementation of Release of Disease-Related Health Information on the Medical Resume of ER Patients - Purnamasari, Iin; Budiaty , Wa Ode Sitty; Muzuh , Mega Ermasari (International Journal of Multidisciplinary Learners, 2025)
Healthcare providers are responsible for maintaining the security of health data contained in medical records from potential loss, damage, falsification, or unauthorized access given that medical information is confidential. Therefore, in the implementation of information release, it is necessary to have approval from the patient himself. This study aims to determine the implementation of the release of disease-related health information on the medical resume of emergency room patients at Baubau City Hospital, using qualitative research methods with a descriptive approach. The data collection technique uses observation and interview methods. The research subjects were 1 doctor, and 3 nurses who were on duty in the ER installation. The object of the study is the implementation of the release of disease-related medical information on the medical resume of the ER patient, data analysis using interactive analysis. The research at Baubau City Hospital confirms that there is an established Standard Operating Procedure (SOP) for the release of medical information, and it is being properly followed. However, a challenge arises when family members seek information about the patient’s condition, as details can only be shared with individuals authorized by the patient. To address this, the hospital informs families about the confidentiality of medical information and emphasizes that only authorized persons can receive it. The study concludes that while the SOP for information release is effectively implemented, managing unauthorized information requests remains a challenge.